Organic compost addition to raw rice husk substrate for tomato (Solanum lycopersicum) hybrid variety cultivation in a leach recirculating system - Carini, Fernanda; Peil, Roberta Marins Nogueira; Marques, Gabriel Nachtigal; Grolli, Paulo Roberto; Souza, Rafaela Schmidt de (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The addition of organic compost (OC) to raw rice husk (RRH) may benefit the production of a tomato crop by conferring a greater buffer capacity and water holding capacity to the substrate in a leach recirculation system. At the same time, the selection of varieties that respond positively to the proposed technology is required. The objective of this work was to study the effects of adding OC to RRH on the physical and chemical properties of substrate [by comparing RRH (100%) and the mixture of RRH (80%) + OC (20%)] and on growth and yield responses of four tomato hybrid varieties [Ivety, Sofhia-F3, Sheila Victoria, and Lumi (Sakata® Seed)]. The chemical and physical properties of substrates, plant dry matter production and partitioning, fruit number, mean weight and yield, and fruit total soluble solids (TSS) content were evaluated. Fruit grading and harvest distribution along the crop cycle were also performed. The addition of OC improved the physical and chemical properties of the substrate. However, it did not affect the major growth and productive characteristics of the crop. All four varieties presented similar growth and fruit yield, but Sheila Victoria stood out as having the highest TSS. The yields were considered high, ranging from 6.3 kg/plant for Sophya and Sheila Victoria, 6.5 kg/plant for Lumi, to 7.6 kg/plant for Ivety. The results indicated that the addition of OC to RRH is unnecessary and that the four varieties adapted similarly to the proposed system.